General Washington's Christmas farewell : a Mount Vernon homecoming, 1783 - Weintraub, Stanley, 1929-2019. (New York : Free Press, 2003)
"One of America's greatest Christmas stories and also one of its very first - from the period between the end of the Revolutionary War and the ratification of the Constitution - was a creation of none other than George Washington. The story isn't just about Washington coming home for Christmas for the first time since the war began, but about the character of our most important Founding Father and about the precedent he set for democratic leadership. It is the story of a loving husband, a beloved military leader, and above all, a humble and great man." "Washington's homeward journey is one of the most moving and inspiring stories from his great and eventful life. When he bade farewell to his troops at Fraunces Tavern in New York City there were no dry eyes. When he reached Congress and gave a retirement speech, it cemented his greatness more fully than had his victory over the British. When he made it to Mount Vernon, finally, on Christmas Eve, it could not have been a happier homecoming."--Jacket.
Beginning the end -- The price of independence -- To New York City -- Reoccupation -- The first farewell -- Fraunces Tavern -- To Philadelphia -- Arts and entertainments -- Toward Annapolis -- Final farewell -- Christmas and after.
Includes bibliographical references and index.
Keywords: Washington, George, -- 1732-1799.; Generals -- Retirement -- United States -- History -- 18th century; Farewells -- United States -- History -- 18th century; Christmas -- Virginia -- Mount Vernon -- History -- 18th century; Generals -- United States -- Biography; Presidents -- United States -- Biography; Washington, George; Geschichte 1783.